1998
DOI: 10.1016/s0022-2275(20)34211-5
|View full text |Cite
|
Sign up to set email alerts
|

Binding of phospholipid transfer protein (PLTP) to apolipoproteins A-I and A-II: location of a PLTP binding domain in the amino terminal region of apoA-I

Abstract: The interaction of plasma phospholipid transfer protein (PLTP) with HDL has not been characterized in detail, although we have reported that the apoA-I/apoA-II molar ratio in the HDL particle influences PLTP-mediated HDL conversion, but not phospholipid transfer. The aim of this study was to examine whether PLTP binds apoA-I or apoA-II, and if this occurs, then determine the PLTP-binding domain of the apoA-I molecule. To study the PLTP/apolipoprotein interaction we used a solid phase ligand binding assay, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 63 publications
2
25
0
Order By: Relevance
“…Several studies have demonstrated that plasma PLTP activity is associated with a subfraction of HDL (27,28) and may interact with the main HDL apolipoprotein, apoA-I (29). The present results and previous work (28) demonstrate that this interaction is largely interrupted by ultracentrifugation in the presence of high ionic strength.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies have demonstrated that plasma PLTP activity is associated with a subfraction of HDL (27,28) and may interact with the main HDL apolipoprotein, apoA-I (29). The present results and previous work (28) demonstrate that this interaction is largely interrupted by ultracentrifugation in the presence of high ionic strength.…”
Section: Discussionsupporting
confidence: 73%
“…phospholipid transfer protein (pltp). PLTP binds both purified apoA-I and apoA-II (62). The PTLP effect on HDL size conversion was seen both in LpA-I and in LpA-I/ A-II (63).…”
Section: Roles In Hdl Structure-function and Metabolismmentioning
confidence: 96%
“…It is possible that the bound lipids play a merely structural role. Inhibition of lipid insertion into the pockets could cause minor changes in the fold of the protein or its molecular interactions with HDL apolipoproteins (38) or phospholipids (15), causing the observed differences in phospholipid transfer activity. In this model PLTP would facilitate the transfer of phospholipids from the donor to the acceptor by bringing these particles in close contact.…”
Section: Discussionmentioning
confidence: 99%